The interaction of students at the Federal Institute of Goiás with medicinal plants and non-conventional food plants - Dutra, Rodrigo Marciel Soares (2023)
The use of medicinal plants in the treatment and cure of illnesses dates back to antiquity and emerged with humanity itself. Medicinal plant is any plant that exerts some therapeutic action on living organisms. Non-conventional food plants (PANC) are commonly called “weeds”, as they flourish among cultivated plants. The PANC are species with great ecological and economic importance, and several species are food, even if currently in disuse by most of the population. Ethnobotany emerges as the interdisciplinary field that comprises the study and interpretation of knowledge, cultural significance, handling and traditional uses of flora elements. This work aims to understand the dynamics of interactions between students from two campuses of the Federal Institute of Education, Science and Technology of Goiás (IFG) with medicinal plants and non-conventional food plants. To this end, a survey was conducted on the Águas Lindas and Senador Canedo campuses, located on the outskirts of the two largest cities in the Midwest. A questionnaire containing 23 questions on the subject was applied to students of all courses offered by the two campuses, accounting for participation of more than 90% of the student public of both units. The results were treated and it was concluded that there is a greater interaction with medicinal plants than with PANC. However, it was noticed that the subject needs to be deepened with these students, given its importance. The IFG can act on several fronts to fill this need, educating for life, for the emancipation of these individuals and contributing to their well-being.